Konsep Kesetaraan Pasangan dalam Pernikahan Pandangan Wahbah Az-Zuhaili dalam Tafsir Nya (Analisis Qs. An-Nur Ayat 26) - Ifrohul Fadhilah; Hasan Bakti Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article discusses the concept of equality of partners in marriage according to the views of Wahbah az-Zuhaili through the interpretation of the QS. An-Nur verse 26 in his tafsir al-Munīr. This verse emphasizes the reciprocal relationship between the moral qualities of an individual and his life partner, that